Efficacy of a Self-managed Cooling Intervention for Pain and Physical Activity in Individuals With Recently Healed Chronic Venous Leg and Diabetic Foot Ulcers: A Randomized Controlled Trial. Issue 4 (4th July 2022) - Kelechi, Teresa J.; Mueller, Martina; Madisetti, Mohan; Prentice, Margaret
Abstract : PURPOSE: This aim of this study was to evaluate the clinical efficacy of a self-managed cooling intervention in individuals with recently healed venous leg ulcers (VLUs) and diabetic foot ulcers (DFUs) on pain reduction and physical activity improvement. DESIGN: A 6-month longitudinal randomized controlled trial. SUBJECTS AND SETTING: The sample comprised 140 individuals with previously healed VLU and DFU who received care in 3 outpatient wound centers in the Southeastern region of the United States. Participants were randomized to the MUSTCOOL or a placebo cooling patch intervention. METHODS: The cooling and placebo interventions comprised cooling or cotton-filled patch application to recently healed skin for 30 minutes, 3 times weekly plus standard of care including compression and leg elevation (participants with VLU) or therapeutic footwear and hygiene (participants with DFU) over a 6-month period. Pain severity and intensity were measured with the Brief Pain Inventory and physical activity with the International Physical Activity Questionnaire, which assessed metabolic equivalent of tasks (METs) in minutes per week. Minutes in walking time per week were assessed with an accelerometer. Data were descriptively analyzed for difference changes in scores from baseline to 6 months post-intervention. RESULTS: Data were analyzed for 81 participants randomized to cooling and placebo groups (VLUs, n = 26/29) and DFU (n = 12/16). Slight reductions in VLU pain severity (−0.5, −0.2) and interference (−0.4, −0.5) and minimal reductions in DFU pain severity (0, −0.1) and interference (0.4/0.1) were achieved. However, pain scores were low to moderate at baseline (mean 4, 0-10 with 10 worst pain possible) in both groups. For physical activity, the MET values showed low physical activity in both groups at baseline with slight improvements noted in VLU cooling and placebo groups (73/799) and DFU (1921/225), respectively. Walking time for the VLU groups improved by 1420/2523 minutes; the DFU groups improved 135/157 minutes, respectively. Findings for outcomes were not statistically significant within or between groups. CONCLUSIONS: Application of the cooling pack compared to placebo was minimally efficacious in reducing posthealing pain and improving function in this posthealed ulcer population. However for pain, scores were initially low; thus outcomes on pain, while lower, were marginal. TRIAL REGISTRATION: The study was prospectively registered with ClinicalTrials.gov on December 10, 2015 (Identifier: NCT02626156), https://clinicaltrials.gov/ct2/show/NCT02626156 .